(untitled) (Dialogos, 2017)
O texto é um comentário sobre os artigos que integram o dossiê “Biografismo”. Busca-se recuperar pontos de contato entre as diferentes abordagens, a fim de elencar aspectos fundamentais referentes Ã s relações entre conhecimento histórico e gênero biográfico na atualidade. Os pontos priorizados são: as ligações entre indivíduo e sociedade, (incluindo-se as noções de “contexto” e “representatividade”), as tensões entre verdade e ficção na construção de narrativas biográficas e a dimensão ética associada Ã s biografias, na qual investiguei a trajetória intelectual do general Edmundo de Macedo Soares. Abstract The multiple challenges of the biography to the historian The text is a commentary on the articles that are part of the "Biographism" dossier. It seeks to recover points of contact between the different approaches, in order to list fundamental aspects regarding the relations between historical knowledge and biographical genre in the present time. The prioritized points are: the links between individual and society (including the notions of "context" and "representativeness"), the tensions between truth and fiction in the construction of biographical narratives, and the ethical dimension associated with biographies.